Roadmap for a Green Financial Policy in Ukraine under the EU Association Agreement - Tetiana Sokolova; Oleksandr Sushchenko; Reimund Schwarze (Helmholtz-Zentrum für Umweltforschung (UFZ), 2019)
This paper examines the prospects and feasibility of using the Association Agreement between Ukraine and the EU as a roadmap for reorienting the Ukrainian brown economy toward a green economy, making use of green financial instruments in the process. The first chapter is dedicated to the concept of green financial policy as well as its main fiscal and market instruments. The second chapter explores in detail the state of climate-related affairs in Ukraine, the country's commitments to numerous international environmental agreements as well as the role of the EU Association Agreement and its place in the Ukrainian economic context. The third chapter considers the political, economic and social measures required to establish a green financial policy. Our central findings are as follows: (1) Although Ukraine has been making progress towards a green financial policy in recent years, there is no doubt that the country needs technical and financial assistance from its European partners. The Association Agreement between Ukraine and the countries of the European Union provides an essential basis for building a green economy in Ukraine. (2) Despite efforts to mobilise internal green financial resources, the Ukrainian Government is struggling with what has already been achieved and is at a crossroads in moving in a different direction. For this reason, local and even non-governmental organisations in Ukraine today have often a greater direct influence on the process of building a green economy than the government itself. Two promising examples of Ukrainian companies seeking a green reputation are the Ukrainian Green Bank (Ukrgasbank) and the large energy company DTEK.
urn:nbn:de:gbv:3:2-112993
Keywords: 330; green economy; sustainable development; low-carbon technology; green finance; environmental taxation; green investment; Ukraine; European Union; Association Agreement; National Action Plan